The Effect of Support On Diet Compliance For Hypertension In The Elderly In Stroke Prevention at Balowerti Community Health Center, Kediri City - Hariyono; Yuly Peristiowati; Arantriwardani (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2024)
Disease hypertension is one of disease degenerative which is often experienced by the next age . Symptoms hypertension appear consequence non-compliance sufferer hypertension in running a hypertension diet . Changes in lifestyle life public globally make​ consumption fresh vegetables and fiber reduced , increased with increasing consumption of salt, fat, sugar increased . Research objectives This is Analyze Influence Support Family According to Friedman's Theory Regarding Compliance Diet Hypertension in Advanced Age In Prevention Stroke Disease in Health Center Balowerti Kediri City . Research design This use approach cross sectional . The population all elderly affected​ hypertension in the Community Health Center Balowerti Kediri City . Sampling technique using systematic random sampling with the sample a total of 65 people. Independent variable support family and dependent compliance with hypertension diet in the elderly . Research instrument use sheet online questionnaire . Data processing includes editing, coding, scoring, tabulating and statistical testing using chi-square . Research results part large (66.7%) respondents get support good family , a total of 37 people almost from half (68.5%) of respondents obedient on hypertension diet . The chi-square test shows that mark significance p-value 0.004 <( 0.05) so H0 is rejected . Research This can concluded that There is Influence support family According to Friedman's Theory to hypertension diet compliance On Next Age In Prevention Stroke Disease In Health Center Kediri City Hall